Construção das personagens femininas em romances de imigração do Rio Grande do Sul - Fuchina, Francieli (2016)
This bibliographic research aims to analyse the construction of two female characters: Frida (Frida Meyer – 1924) and Lore (Um Rio imita o Reno – 1939). The work uses Cultural and Gender Studies and establishes the relation between fictional and historical discourses. This essay highlights the discoursive resources used by narrators that have formed the image of the German women who represent the migration and the colonization process in Rio Grande do Sul.